Demographic and net primary productivity dynamics of primary and secondary tropical forests in Southwest China under a changing climate - Oo, STT; Panthi, S; Fan, Z; Song, X; Zhang‐Zheng, H; Zaw, Z; Lu, H; Chen, H; Deng, Y; Zhao, R; Lin, H; Fu, P (Wiley, 2024)
Tropical forests are major carbon sinks on the Earth's land surface. However, our understanding of how the demographic rate and carbon sink capacities of tropical forests respond to climate change remains limited. In this study, we investigated the impacts of environmental drivers on forest growth, mortality, recruitment, and stem net primary productivity (NPPstem) over 16 years at five tropical forest plots in Xishuangbanna, Southwest China. These plots are along a successional gradient spanning three tropical secondary forests (tropical secondary forest‐1 [TSF‐1], tropical secondary forest‐2 [TSF‐2], and tropical secondary forest‐3 [TSF‐3]) and two primary forests (tropical rainforest [TRF] and tropical karst forest [TKF]). Our results showed that early successional secondary forests (TSF‐2 and TSF‐3) had higher diameter growth rates and relative mortality rates. An extreme drought event during 2009–2010 reduced the growth rate, relative recruitment rate, and NPPstem for most plots while increasing mortality in early successional forest plots. We observed significant negative effects of maximum temperature (Tmax) on NPPstem and diameter growth rate across all plots. Additionally, we found that precipitation had significant positive effects on diameter growth rate across all plots. Furthermore, tree mortality increased with rising Tmax, whereas precipitation significantly enhanced tree recruitment. Our findings highlight the vulnerability of tree growth, mortality, recruitment, and productivity in tropical forests to extreme drought events in Southwest China. Continued climate warming and more frequent droughts will induce higher mortality rates and impede growth, thus reducing the carbon sink capacity of tropical forests, especially in early successional stage tropical secondary forests.